Characterization of mangrove species using ALOS-2 PALSAR in Hai Phong city, Vietnam. (June 2016) - Pham, Tien Dat; Yoshino, Kunihiko
Abstract: Hai Phong city is located in the Northern coast of Vietnam where the mangroves are distributed between zone I and zone II among the four mangrove zones in Vietnam. This city is vulnerable to rising sea levels associated with climate change and tropical cyclones, which are forecasted to become more severe due to the impact of climate change. In the past, mangrove forests in this city have decreased markedly because of over expansion of shrimp farming. Thus, identification of mangrove forests is important to monitor and support mangrove conservation and management in the coastal zone. The objectives of this research were to identify the locations of mangrove and characterize mangrove species in Hai Phong using HH and HV backscatters of the Advanced Land Observing Satellite 2 (ALOS-2) with enhanced Phased Array L-band Synthetic Aperture Radar (PALSAR). Image segmentation was used to identify the locations of mangrove forests. Moreover, Geographic Information System (GIS) was applied to update current status of mangrove species in 2015. The results showed that the means of HH and HV backscatter coefficients of K. obovata are lower than S. caseolaris. K. obovata has HH value around -13.9 dB until -10.3 dB and HV value around -20.6 dB until -16.2 dB. Higher HH values between about -14.9 dB and -6.8 dB and HV values between roughly -20.6 dB and -14.3 dB have observed by S. caseolaris. The total area of mangrove forest in Hai Phong in the year 2015 was around 4084 hectares, of which S. caseolaris occupied over 68% and mixed mangrove species was approximately 25.6%. This research indicates the potential for the use of L-band ALOS-2 PALSAR in characterizing mangrove forest species in the coastal zone.